1999
DOI: 10.1016/s0886-3350(99)80018-2
|View full text |Cite
|
Sign up to set email alerts
|

Cataract progression in patients with atopic dermatitis

Abstract: Patients with facial atopic dermatitis, contact lenses, or both may rub their eyes more frequently than those with lesions on other body parts, increasing their risk of cataract progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…23 In another study, authors reported that 10-25% of patients with atopic dermatitis had early onset of cataract that often occurred during exacerbations of the disease. 29 In another study, 25% of patients with atopic dermatitis had cataract, with PSC cataract being the most common type (50%) followed by anterior subcapsular cataract (25%) and total opacities (12.5%). 30,31 These authors also noted rapid progression of cataract during periods when the skin disease was active.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…23 In another study, authors reported that 10-25% of patients with atopic dermatitis had early onset of cataract that often occurred during exacerbations of the disease. 29 In another study, 25% of patients with atopic dermatitis had cataract, with PSC cataract being the most common type (50%) followed by anterior subcapsular cataract (25%) and total opacities (12.5%). 30,31 These authors also noted rapid progression of cataract during periods when the skin disease was active.…”
Section: Discussionmentioning
confidence: 93%
“…30,31 These authors also noted rapid progression of cataract during periods when the skin disease was active. 29,30 A breakdown of the blood-aqueous barrier and frequent eye rubbing may also be contributory factors. 32,33 A literature review of population-based studies on risk factors for cataract has failed to reveal atopy as a risk factor for the development of cataract even in young and age-related cataract.…”
Section: Discussionmentioning
confidence: 99%
“…24 AD is associated with AS cataracts, but differentiating AD-associated cataracts from corticosteroidinduced cataracts may be difficult, because PS cataracts or a combination of both types have also been described as associated with AD. [25][26][27] Furthermore, it may be difficult to differentiate early lens opacities in the posterior lenticular pole as steroid-induced or other types. 28 It is not known by which route topical corticosteroids induce glaucoma or cataract.…”
mentioning
confidence: 99%
“…[1][2][3] The ocular complications of AD include cataract, retinal detachment, and corneal changes such as keratoconus. Many hypotheses have been proposed to explain the pathogenesis of atopic cataract and retinal detachment.…”
mentioning
confidence: 99%
“…It is thought that patients with facial atopic dermatitis habitually rub or scratch their eyes because of severe itching and that this is a crucial factor contributing to the pathogenesis of cataract and retinal detachment. [1][2][3][4][5][6][7][8][9] However, the etiology of corneal complications in AD, including keratoconus, has not yet been clarified. A major reason may be that there is no appropriate animal model of AD-related corneal complications.…”
mentioning
confidence: 99%